Assessment of Antimicrobial Activity, Membrane Integrity, and Oxidative Stress of Green Synthesized Silver Nanoparticles: In Vitro and Molecular Docking Studies - Sebti, Sarra; Barhouchi, Badra; Meskaldji, Samir; Houicha, Haroun; Bagci, Eyup; Bendif, Hamdi; Garzoli, Stefania (Wiley-V C H Verlag Gmbh, 2026)
Silver nanoparticles were synthesized using Acacia karroo aqueous leaves extract for the first time, as evidenced by a characteristic UV-Vis absorption peak at 424 nm. Spherical morphologies were observed using transmission electron microscopy (TEM) and scanning electron microscopy (SEM), with mean diameters determined to be 33 nm. XRD analysis validated the crystalline nature of the nanoparticles, with characteristic peaks at 2 theta values of 38.19 degrees, 44.34 degrees, 46.21 degrees, 64.35 degrees, 77.54 degrees, and 81.39 degrees corresponding to the (111), (200), (211), (220), (311), and (222) planes of face-centered cubic silver. Synthesized AgNPs demonstrated moderate anti-Candida albicans and antibacterial properties against the tested strains. Overall, AgNPs-treated Staphylococcus aureus and Escherichia coli showed higher levels of cell leakage, protein content, and malondialdehyde concentrations than untreated cells. Molecular docking studies demonstrated strong interactions between silver and microbial proteins, with the highest binding affinity observed for protein 5NG5, followed by 5BNM and 3HUM.
Keywords: Acacia Karroo; Agnps; Antimicrobial Activity; Lipid Peroxidation; Molecular Docking; Oxidative Stress